Media Literacy, Social Connectedness, and Digital Citizenship in India: Mapping Stakeholders on How Parents and Young People Navigate a Social World - Sarwatay, Devina; Raman, Usha; Ramasubramanian, Srividya (Frontiers in Human Dynamics, 2021)
The ubiquity of digital and social media has led to considerable academic debate regarding their role in the lives of children and adolescents. The Global North, especially USA and Europe, has largely led this discussion in matters of research methods and approaches, as well as on conversations around screen time, wellbeing, media literacy, and digital citizenship. However, it is not clear to what extent and how these Anglo-Eurocentric approaches to digital literacy and social connectedness translate to the various local realities of the Global South, where increasing numbers of young people have either direct or indirect access to social media and the internet, but occupy very different social contexts. In India, for instance, low cost mobile phones, cheap data plans, and vernacularization of content have furthered access cutting across socioeconomic strata. What specific research priorities might emerge in this context? Which methods can be employed to study these issues? How can we contextualize existing knowledge to help support young people and their parents maximize the benefits of this digital/social world even as we take into account the nuances of the local? In this paper, we mapped local stakeholders and shared insights from in-depth personal interviews with community leaders from civil society, research, and advocacy as well as professionals working with young people and parents in India as their work addresses some of these important questions. A thematic analysis of interview data helped the researchers scope out issues like lack of child-centered-design, dearth of knowledge about the opportunities and risks of social media among parents, and confusion on how to navigate this digital/social world. Suggestions about children’s wellbeing, including what parents could do about this, the possibility of and the problems with regulation, and the need to focus on how parents can foster trust and a meaningful connection with young people that would frame their engagement with technology are made. Future research should consider these relationships within the new context of the COVID-19 pandemic and related issues such as degrees of digital connectivity and access, social isolation, virtual schooling, and parents working from home.